"I Say I Work at the University:" Norwegian Professors and Passing as Interaction Ritual. Issue 3 (4th January 2022) - Vassenden, Anders; Rusnes, Ingrid
Abstract : This paper extends the study of passing to a privileged identity. From qualitative interviews, we examine Norwegian professors' everyday self‐presentation. When in new encounters, like meeting other parents through their children's leisure activities, our respondents' leave their occupation and especially title undisclosed before cautiously negotiating possible disclosure. The existing literature mostly highlights passing that happens for self‐protection. While (soft) self‐protection is one concern for professors, they also pass for additional reasons: protecting interactants from insecurity or discomfort and preventing imbalance and "fuss." Theoretically, we combine Goffman's treatise of passing with interaction ritual and facework. We discuss whether this analytical model may also help clarify instances of stigma passing and consider the consequences of privilege passing for social inequality.